Anion–π catalysis on carbon allotropes - Gutiérrez López, M. Ángeles; Tan, Mei-Ling; Renno, Giacomo; Jozeliūnaitė, Augustina; Nué-Martinez, J. Jonathan; Lopez-Andarias, Javier; Sakai, Naomi; Matile, Stefan (Beilstein Journal of Organic Chemistry, 2023)
Anion–π catalysis, introduced in 2013, stands for the stabilization of anionic transition states on π-acidic aromatic surfaces. Anion–π catalysis on carbon allotropes is particularly attractive because high polarizability promises access to really strong anion–π interactions. With these expectations, anion–π catalysis on fullerenes has been introduced in 2017, followed by carbon nanotubes in 2019. Consistent with expectations from theory, anion–π catalysis on carbon allotropes generally increases with polarizability. Realized examples reach from enolate addition chemistry to asymmetric Diels–Alder reactions and autocatalytic ether cyclizations. Currently, anion–π catalysis on carbon allotropes gains momentum because the combination with electric-field-assisted catalysis promises transformative impact on organic synthesis.
Keywords: anion–π interactions; autocatalysis; catalysis; carbon nanotubes; Diels–Alder reactions; electric-field-induced catalysis; electromicrofluidics; enolate addition; ether cyclizations; fullerenes